The effect of ownership structure on social and environmental disclosure in Indonesia - Siti Jubaedah; Doddy Setiawan (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2023)
This study examines the effect of ownership structure with management ownership, foreign ownership, dispersed ownership and block ownership sub-variables on social and environmental disclosure. The Global Reporting Initiative (GRI) disclosure framework was adopted to extract social and environmental disclosures. The research method used is a quantitative method. The population in this study are manufacturing sector companies listed on the Stock Exchange Indonesia in 2018-2020. A total sample of 243 was obtained using a judgment sampling technique with a sample of 81 companies. The analytical method used in this research is multiple linear regression. The results of the analysis show that on average, social and environmental disclosure in manufacturing companies in Indonesia is still quite low. This research shows that there is an influence of management ownership, foreign ownership, and block ownership on social and environmental disclosure but not significant for dispersed ownership. The results of the analysis show that foreign ownership has a fairly strong positive influence on social and environmental disclosure. It was found that foreign ownership dominates the ownership structure by 97.59%, so that company managers must give more consideration to ownership structure, especially foreign ownership and international environmental standards to design good and effective social and environmental disclosure strategies. This study may be of interest to regulators as material for consideration in making investment policies, especially foreign investment regulations.